English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Find the x-intercepts. y= x^2 - 7x + 7

Can someone show me the steps to doing this problem?

2006-11-23 14:46:08 · 8 answers · asked by George F 1 in Science & Mathematics Mathematics

8 answers

because of the fact the X-axis has a pair (x,y) with y=0 it somewhat is each and all the dots on the axis have a pair (x,0). with the intention to uncover the respond you definetly could have Y=0 because of the fact in basic terms then will the interception be on the x-axis. so because of the fact of which you are going to choose "y=0" and "y=x^2 +7x +4" so once you combine you have 0=x^2 +7x +4 while resolved with the quadratic formula (you've none, one or 2 solutions) as a effect we've 2 answer for the x area of the pair (x,y) (bear in ideas all of us understand y=0) so the 1st answer is x1= -6.36 the 2d answer is x2= -0.06 the element the place it somewhat is intercepted are (-6.36,0) and (-0.06,0) because of the fact Y=0 for each and all the dots on the x-axis

2016-10-13 00:17:52 · answer #1 · answered by schwalm 4 · 0 0

For x intercepts set y = 0

0 = x^2 - 7x + 7
x = [7 +/- sq.root(49 - 28)]/2
x = [7 +/- sq.root(21)]/2

2006-11-23 14:52:16 · answer #2 · answered by Anonymous · 0 0

x intercepts are where the curve cuts the x axis where the y coordinates will be zero
so setting y=0
x^2-7x+7=0
x=[7+/-rt49-28)]/2
=(7+rt21)/2 and (7-rt21)/2
so the x interceptsare
(0,(7+rt21)/2);(0,(7-rt21)/2)

2006-11-23 15:02:16 · answer #3 · answered by raj 7 · 0 0

to find the X intercepts u need to set Y equal to zero.

1) 0 = x^2 - 7x + 7

2) now you use the quadradic equation -B +/- [(the sqaure root of) B^2 - 4AC] / 2A

3) 7 +/- [(the square root of) 49 - 28]/ 14

4) 7 +/- [the square root of 21]/14

and thats ur answer

2006-11-23 14:54:19 · answer #4 · answered by brookbabe90 5 · 0 1

the x-interecepts are the same as the "solutions" which are the same as the "zeroes" which are the same as how it can be factored down. You can factor it into (x+7)(x-1)=0

From that you can divide both sides by (x+7) and get x-1=0
You can also divide both sides by x-1 to get x+7=0

So x= 1 and x= -7 are the two solutions

2006-11-23 14:54:27 · answer #5 · answered by Erik N 2 · 0 1

when y=0
0=x^2 - 7x + 7
use quad formula
x= 1.2087 and 5.7912

2006-11-23 14:52:38 · answer #6 · answered by      7 · 0 0

x^2 - 7x + 7 = 0

x = (-b ± sqrt(b^2 - 4ac))/(2a)

x = (-(-7) ± sqrt((-7)^2 - 4(1)(7)))/(2(1))
x = (7 ± sqrt(49 - 28))/2
x = (7 ± sqrt(21))/2

x = (1/2)(7 ± sqrt(21))

2006-11-23 16:02:08 · answer #7 · answered by Sherman81 6 · 0 0

fedest.com, questions and answers